PENANAMAN NILAI KARAKTER DAN MULTIKULTURAL DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 2 BLORA - Nugraha, Arya Sena; Salam, Rudi (Sosiolium : Jurnal Pembelajaran IPS, 2021)
Junior High School 2 Blora is a school with a diversity of students and teachers in the school, ranging from culture, language, religion, social status, gender, ability, age and race. The purpose of this study was to find out how to instill character and multicultural values ​​in social studies learning and the supporting factors for inculcating character and multicultural values ​​in JHS 2 Blora. This type of research is qualitative research. The results of this study indicate that the cultivation of character and multicultural values ​​can be applied in social studies learning by integrating materials that contain character values ​​and multicultural values ​​in them. Instilling character and multicultural values ​​in social science learning at JHS 2 Blora through teaching and learning activities such as group work, utilizing the environment as a learning resource and using the lecture method. The character values ​​inculcated in social studies learning are taken from the main values ​​in the PPK Movement program and for multicultural values ​​it is directly guided by the values ​​of tolerance, equality/equality, kinship/brotherhood, unity and justice. The cultivation of character and multicultural values ​​is supported by the existence of supporting factors in planting, which is carried out in the learning process in the school environment that is directly related to students. SMP Negeri 2 Blora adalah sekolah dengan keberagaman siswa dan guru di dalam sekolah, mulai dari budaya, bahsa, agama, status sosial, gender, kemampuan, umur dan ras. Tujuan penelitian ini untuk mengetahui cara menanamkan nilai karakter dan multikultural dalam pemelajaran IPS dan faktor penunjang penanaman nilai karakter dan multikultural di SMP Negeri 2 Blora. Jenis penelitian ini adalah penelitian kualitatif. Hasil penelitian ini menunjukkan bahwa penanaman nilai karakter dan multikultural dapat diterapkan dalam pembelajaran IPS dengan pengintegrasian materi-materi yang mengandung muatan nilai karakter dan nilai multikultural di dalamnya. Penanaman nilai karakter dan multikultural dalam pembelajaran ilmu pengetahuan sosial di SMP Negeri 2 Blora melalui kegiatan belajar mengajar seperti kerja kelompok, memanfaatkan lingkungan sebagai sumber belajar dan penggunaan metode ceramah. Nilai karakter yang ditanamkan dalam pembelajaran IPS diambil dari nilai utama dalam program Gerakan PPK dan untuk nilai multikultural berpedoman langung pada nilai toleransi, kesamaan/ kesetaraan, kekerabatan/ persaudaraan, persatuan dan keadilan. Penanaman nilai karakter dan multikultural didukung dengan adanya faktor penunjang dalam penanaman, yakni dilaksanakan dalam proses pembelajaran di lingkungan sekolah yang berkaitan secara langsung dengan peserta didik.